Reliability of fetal nasal bone length measurement at 11-14 weeks of gestation - Suwanrath Chitkasaem; Pruksanusak Ninlapa; Kor-anantakul Ounjai; Suntharasaj Thitima; Hanprasertpong Tharangrut; Pranpanus Savitree (BMC, 2013)
Abstract Background Nasal bone assessment has been incorporated into Down syndrome screening in first trimester. Several studies have established the normal reference values for fetal nasal bone length in the first trimester, which were found to be varied by population. However, the study on reliability of nasal bone length measurement was limited with contradictory results. This study aimed to investigate the reliability of fetal nasal bone length measurement at 11-14 weeks of gestation in the Thai population. Methods A total of 111 pregnant women at 11-14 weeks of gestation attending for the routine first-trimester ultrasound examination were recruited. Each case was measured separately by two examiners. Examiner 1 performed the first measurement in all cases; any of the other 5 examiners consecutively performed the second measurement. Three independent measurements were performed by each examiner and they were blinded to the results of the others. Intraobserver and interobserver variabilities were evaluated with the intraclass correlation coefficient (ICC). Results Nasal bone measurement was successfully performed in 106/111 cases (95.5%) by at least one examiner; 89 cases were performed by two examiners. The intraobserver variability was excellent for all examiners (ICC, 0.840-0.939). The interobserver variability between different pairs of examiners varied from moderate to excellent (ICC, 0.467-0.962). The interobserver variability between examiner 1 and any other examiner was good (ICC, 0.749). The Bland-Altman plot of the interobserver differences of nasal bone length measurements between examiner 1 and any other examiner showed good agreement. Conclusions The reliability of the fetal nasal bone length measurement at 11-14 weeks of gestation was good. The nasal bone length measurement was reproducible. Ethnicity has an effect on fetal nasal bone length, but reliability of nasal bone length measurement is critical to accuracy of screening and should be audited on an ongoing basis.